Stone-free rate of laser lithotripsy for large pediatric stones: 15-year experience from a tertiary endourology pediatric center - Dassanayake, Sohani N.; Jahrreiss, Victoria; Griffin, Stephen; Somani, Bhaskar K. (Therapeutic advances in urology, 2025)
Plain language summary Safety and outcomes of large paediatric stones treated by ureteroscopy Large paediatric renal stones are often treated by percutaneous stone surgery procedure. In this paper we look at Ureteroscopy as a treatment for these large paediatric stones. Our data shows a good stone free rate with low risk of complications. Perhaps, ureteroscopy will offer an alternate treatment for these vulnerable age group especially for large renal stones.